Carga de carregamento de molares tratados endodonticamente restaurados com cobertura de cúspide em resina composta e pino de fibra de vidro transfixado horizontalmente - Andrade, Jonas Pereira (2021)
Objective: To evaluate the fracture strength of endodontically treated molars with MOD preparations restored with composite resin with or without cusps cover and fiberglass post transfixed horizontally. Materials and Methods: Seventy sound extracted third molars were randomly divided into 7 groups (n = 10). Group H (sound) and other groups received the following procedures after endodontic treatment: C (MOD), P (MOD + post), R (MOD + resin), PR (MOD + resin + post), FR (MOD + resin cusp cover), PFR (MOD + resin cusp cover + post). The samples were subjected to mechanical cycling (500 thousand cycles with a load of 200 N). Afterwards, they received the maximum load test with a speed of 1 mm / min. The failures were classified as repairable and irreparable. Results: The data were submitted to the Shapiro-wilk test, followed by one-Way Anova and Tukey at the 95% confidence level. Group H had the highest average in Newtons (4359) a, followed by the other groups: PFR (3226) e, FR (2859) e, PR (2116) d, R (1480) c, P (1023) bc, C (835) b. Conclusions: The PFR and FR groups with resin cusp cover obtained the highest fracture strength results. Clinical Relevance: The use of the horizontally transfixed fiberglass post has a beneficial effect on extensively compromised endodontically treated teeth.